Cyber Security Behavior of E-Commerce Application Users - Hensy Watung, Leyri Nayoan, Avandi E. Untu (JR Education, 2021)
E-Commerce technology is a business mechanism that works electronically by focusing on online business transactions and has the opportunity to build more human and personalized relationships with customers without depending on space and time. The purpose of this study was to determine to what extent, the influence of Cyber ​​Crime behavior on users of e-commerce applications that affect the level of trust of users of E-Commerce transaction services. The data used in this study is primary data. The data analysis method used is quantitative using a Likert scale. The population in this study was 30 respondents as the research sample, using google form. The results based on the analysis showed that e-commerce users bear a lot of the risk is added to the level of trust of E-Commerce users, making Cybercrime behavior is still very difficult to anticipate by users of E-Commerce transaction services, has a negative and significant effect